(untitled) (CAHIERS MAGELLANES-NS, 2024)
Hydroecological monitoring of fish ponds fishery farm located in Kuichirchik district of Tashkent region was carried out as part of Titova Nataliya’s dissertation research on the topic: “Assessing the influence of environmental factors on the safety of fish products (live fish) produced in fish farms in the Tashkent region” under the guidance of PhD, senior researcher Kurbanov Abdulla and candidate of biological sciences, associate professor Atabaeva Nargis.